What Should the Goals Be? Employment Equity for Female Faculty in Canada - Blakely, John H. (Canadian Journal of Higher Education, 1989)
This paper investigates the process of setting employment equity goals and timetables for female faculty in Canadian universities. First, the paper identifies the conditions under which a goal of a 50-50 balance between men and women faculty members by the year 2000 can be achieved. Second, it identifies criteria for evaluating the reasonableness of this goal. Third, given that such criteria as external availability, impact on labour demand and fairness suggest that this goal may not be reasonable, the question becomes: what should the goals be? The paper addresses this question by analyzing the impact of alternative hiring targets (reflecting alternative assumptions about external availability) on the gender composition of faculty in the year 2000. These hiring targets range from an extremely conservative 16.8% female to an optimistic 44.4% female. Under appropriate assumptions, these yield gender composition estimates ranging from 17.5% to 35.4%. While recognizing that availability will vary across universities, it is hoped that the estimates provided herein will inform debates on setting employment equity goals: l)by illustrating and elaborating on a methodology for establishing goals and timetables; and 2) by providing lower-bound and upper-bound estimates (along with estimates based upon moderate assumptions) to illustrate the range of possibilities under Canadian employment equity policy.